A Highly Expressing, Soluble, and Stable Plant-Made IgG Fusion Vaccine Strategy Enhances Antigen Immunogenicity in Mice Without Adjuvant - Diamos, Andrew G.; Pardhe, Mary D.; Sun, Haiyan; Hunter, Joseph G. L.; Kilbourne, Jacquelyn; Chen, Qiang; Mason, Hugh S. (Frontiers in Immunology, 2020)
Therapeutics based on fusing a protein of interest to the IgG Fc domain have been enormously successful, though fewer studies have investigated the vaccine potential of IgG fusions. In this study, we systematically compared the key properties of seven different plant-made human IgG1 fusion vaccine candidates using Zika virus (ZIKV) envelope domain III (ZE3) as a model antigen. Complement protein C1q binding of the IgG fusions was enhanced by: 1) antigen fusion to the IgG N-terminus; 2) removal of the IgG light chain or Fab regions; 3) addition of hexamer-inducing mutations in the IgG Fc; 4) adding a self-binding epitope tag to create recombinant immune complexes (RIC); or 5) producing IgG fusions in plants that lack plant-specific β1,2-linked xylose and α1,3-linked fucose N-linked glycans. We also characterized the expression, solubility, and stability of the IgG fusions. By optimizing immune complex formation, a potently immunogenic vaccine candidate with improved solubility and high stability was produced at 1.5 mg IgG fusion per g leaf fresh weight. In mice, the IgG fusions elicited high titers of Zika-specific antibodies which neutralized ZIKV using only two doses without adjuvant, reaching up to 150-fold higher antibody titers than ZE3 antigen alone. We anticipate these findings will be broadly applicable to the creation of other vaccines and antibody-based therapeutics.